Wheat Stubble Height on Subsequent Corn and Grain Sorghum Crops - A. Schlegel (Kansas Agricultural Experiment Station Research Reports, 2015)
A field study initiated in 2006 was designed to evaluate the effects of three wheat stubble heights on subsequent grain yields of corn and grain sorghum. Corn yields in 2014 were similar to the long-term average, while sorghum yields were greater than the long-term average. Taller cut stubble in 2014 increased biomass production of corn and yield for grain sorghum. When averaged across 2007 through 2014, corn grain yields were 9 bu/a greater when planted into either tall or strip-cut stubble than into low-cut stubble. Average grain sorghum yields were not significantly affected by wheat stubble height. Water use efficiency was greater for taller cut stubble for both corn and grain sorghum. Harvesting wheat shorter than necessary causes a yield penalty for the subsequent row crops, especially dryland corn.
Keywords: wheat stubble; water use efficiency; fertility; grain sorghum; corn; rotations